2017
DOI: 10.1016/j.smallrumres.2016.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of parasite resistance to commonly used commercial anthelmintics in meat goats on humid subtropical pasture

Abstract: Anthelmintic-resistant gastrointestinal nematode parasites are a threat to small ruminant industry sustainability. Meat goat does were administered one of four anthelmintics orally (ivermectin (n = 18), moxidectin (n = 18), levamisole hydrochloride (n = 17), or albendazole (n = 19)) or water (n = 18). Fecal samples were collected pretreatment and 12 days post-treatment. Fecal egg counts (FEC) were determined by the modified McMaster technique. The FEC reduction percentages (FECR%) were calculated using three e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…reported higher rates of clinical endoparasitism for Boer does than for Kiko and Spanish does. In agreement with the current study, 2 recent reports from this location (Goolsby et al, 2017;Wang et al, 2017) reported no differences between Kiko and Spanish does for FEC.…”
Section: Fecal Egg Count and Packed Cell Volumesupporting
confidence: 93%
See 1 more Smart Citation
“…reported higher rates of clinical endoparasitism for Boer does than for Kiko and Spanish does. In agreement with the current study, 2 recent reports from this location (Goolsby et al, 2017;Wang et al, 2017) reported no differences between Kiko and Spanish does for FEC.…”
Section: Fecal Egg Count and Packed Cell Volumesupporting
confidence: 93%
“…FAMACHA scores (a system of classifying eye color to detect endoparasite-induced anemia in small ruminants; Kaplan et al, 2004) are negatively correlated with PCV. Selecting and using genetically resistant goat breeds suitable to the particular environment could be an effective way to reduce endoparasitic loads, particularly since anthelmintic use is becoming a less reliable option for meat goat managers (Goolsby et al, 2017). Problems may arise if introduced goat breeds exhibit heightened sensitivity to endoparasites in a given production environment.…”
Section: Fecal Egg Count and Packed Cell Volumementioning
confidence: 99%
“…The 5% LMS hydrochloride resistance traits observed in some farms may be due to the low efficacy against immature stages of nematodes in general (4), i.e., the larvae residing in the gastrointestinal tract may have matured and started producing eggs (33). The results obtained in the present study corroborate the findings in the state of Ceará (4).…”
Section: Discussionsupporting
confidence: 84%
“…Attempts at controlling gastrointestinal parasitism by using chemical substances indiscriminately without epidemiological knowledge [9] has given rise to anthelmintic resistance and chemical traces being present in both food and the environment [10]. This anthelmintic resistance has been demonstrated in different parts of the world [11][12][13][14][15][16]. In Colombia, multiple resistance in gastrointestinal nematodes (H. contortus, Trichostrongylus spp., and Cooperia spp.)…”
Section: Introductionmentioning
confidence: 99%